Cognitive Accessibility and Support in Special Education - Miguel A. Guillomía; José Ignacio Artigas; Jorge L. Falcó (Sensors, 2021)
This work describes an assistive technology development for cognitive support and training to be used by children of special education schools in Spain. Design is based on and guided by cognitive support findings coming from a long-term collaboration of a team of engineers (University of Zaragoza) and special education teachers (Alborada Special Education School, Zaragoza). The description starts by providing a structure of such findings in five cognitive-social areas (interface usability, virtual representations understanding, time orientation, self-awareness, and social interaction). Design requirements are extracted by applying those findings to four support services (home control, time orientation, behavior contention, and context anticipation). Technological system description follows, together with the degree of implementation and testing for each service. A major result is the benefit of using a services interface with the same structure and appearance as the alternative and augmentative communication system that children are already acquainted with. Based on regulatory conditions, the needed flexibility, and reduced available budgets, this support platform is built on mainstream technology and low-cost single-board computers with standard databases and free software packages. Results show evidence of benefit in children’s cognitive and social performance, in addition to offering a technological tool for deeper educational research.